PERENCANAAN STRATEGIS PENJAMINAN MUTU DAN KINERJA LEMBAGA PENDIDIKAN ISLAM - Asykriyah Laily Rizki; Samsul Susilawati (PT. Hasba Edukasi Mandiri, 2025)
Planning strategies play a fundamental role in ensuring the quality and improving the performance of Islamic educational institutions amidst the dynamics of change and increasingly complex demands for quality education. This study aims to examine the role of planning strategies in ensuring educational quality and ensuring its impact on the performance of Islamic educational institutions. The research method used is a qualitative approach with a library research method, through analysis of various literature sources in the form of books, scientific journals, and relevant documents related to planning strategies, educational quality, and institutional performance. The results of the study indicate that planning strategies function as a primary instrument in formulating the vision, mission, objectives, and strategies of Islamic educational institutions in a systematic and directed manner. The implementation of planning strategies integrated with a quality assurance system can increase the effectiveness of the educational process, strengthen the culture of quality, and encourage continuous improvement in institutional performance. Thus, planning strategies are not only administrative documents, but also serve as an operational basis for managing the quality and performance of Islamic educational institutions.